Implementation of Green Accounting to Concern For The Working Environment of Garment Micro, Small and Medium Enterprises in Gerbang Kertasusila - Siti Maisyaroh; Salija Ridayati; Rr Jihan Faadhilah Yuwandono; Maria Yovita R. Pandin (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the level of understanding and concern of Micro, Small and Medium Enterprises in the gate Garment ethical paper relating to the application of green accounting in its business. Green Accounting is the development of accounting information, which has its own role through voluntary reporting in the company's financial statements related to environmental costs. Observation,interview and documentation techniques were used to collect research data. Data analysis in this qualitative descriptive research using Miles and Huberman data analysis model in (Sugiyono, Metode Penelitian Kuantitatif, Kualitatif, dan R&D., 2017) specifically reduces data, presents data, then makes conclusions. The results of this study indicate that two out of three Micro, small and medium Garment business actors in Gerbang Kertasusila understand and understand about good care in maintaining the work environment as a form of green accounting. Although for details about the expenditure of business costs garment and the environment they have not telesuri in detail but they realize that the environmental cost is a responsibility that is loaded on the financial statements of their businesses that do not include details, but they recognize that the environmental cost is the responsibility of reporting on their business finance research.